Influence of product risk and purchasing risk on further online purchase in C2C market - Puška, Adis; Šadić, Sead; Stovrag, Jasmin (Oeconomica Jadertina, 2018)
With the development of technology and the emergence of the Internet, new markets for buying and selling have been created. Selling on the Internet was not done solely by business entities but also by individuals who started selling their products, hence gave rise to C2C purchase. This paper investigates how the risks of online purchase affect the intention of consumers further purchasing. The survey was carried out in the territory of Bosnia and Herzegovina (BH) and included 419 consumers. The conceptual model included six variables: purchase risk, product risk, online purchase application, online purchase self-efficiency, online purchase value, and further purchase intent. The established model was tested using the Structural Equation Model (SEM) and it was proven that the risks of online purchases do not affect directly the further purchase intent, but they indirectly affect other variables. Research has shown that consumers who are self-efficient in their purchases demonstrate greater intention for further online purchases, as well as consumers who find online shopping easier. Theoretically, this work contributes to a better understanding of how online shopping risks affect the intention of further online shopping in the C2C market. Also, paper in a practical way contributes to understanding the behavior of consumers on the C2C market, which can be used by sellers to improve this aspect of online purchase.
Keywords: online purchase; C2C market; purchase risks; product risks; further purchase intention; Structural Equations Model